Events and figures of the Russian Revolution through the prism of Mariátegui - García Higueras, Gabriel (2019)
The article reviews the journalistic work and the conferences of José Carlos Mariátegui about the Russian Revolution. The selection of articles analyzed is mainly about the policy of the Soviet Government and its diplomatic actions, the cultural work of the Revolution and the debates in the Communist Party of the Soviet Union during the 1920s. In addition, it refers to Mariátegui’s evaluations of some of the main political leaders of the Soviet Republic; in particular, his writings on Leon Trotsky are analyzed.